Elucidation of synergistic interactions between anionic polysaccharides and hemp seed protein isolate and their functionalities in stabilizing the hemp seed oil-based nanoemulsion - Gholivand, Somayeh; Tan, Tai Boon; Mat Yusoff, Masni; Choy, Hew Weng; Teow, Shuh Jun; Wang, Yong; Liu, Yuanfa; Tan, Chin Ping (Elsevier B.V., 2024)
This study aimed to enhance the physical stability of hemp seed oil (HSO) nanoemulsions stabilized by hemp seed protein isolate (HPI)-polysaccharides (carrageenan, alginate, gum arabic and pectin) complexes. Extensive investigations were conducted to evaluate the surface charge characteristics of HPI and polysaccharides, along with an assessment of their binding strength and complex formation. The researchers also examined various influential factors such as polysaccharide type and concentration, nanoemulsion droplet size and charge, environmental stresses, shearing rate, and creaming stability on the HSO nanoemulsions stabilized using HPI-polysaccharide emulsifiers. The results demonstrated that the main influencing parameters were polysaccharide type and concentration. In addition, all HPI (0.5 (w/v)-polysaccharide (0.01 (w/v)) nanoemulsions exhibited significant resistance to droplet aggregation and creaming, even under thermal treatment (≤100 °C). This stability can be attributed to the synergistic effects of the mixed emulsifiers with opposite surface charges, which resulted in nanoemulsions with a positive charge under optimal pH conditions (pH = 3 for carrageenan and 3.5 for other polysaccharides) due to repulsive forces between droplets. Notably, only the HPI-alginate nanoemulsion reveals stability across all salt levels (≤ 500 mM), while the other nanoemulsions remained stable solely at low NaCl concentrations (≤ 200 mM). This exceptional stability can be attributed to the alginate flexibility and formation of a compact complex between HPI at the surface of the nanoemulsion droplets. This study's findings carry significant implications for the food and beverage industries, especially regarding the use of HPI as a functional food ingredient. Furthermore, HPI-alginate nanoemulsions offer great potential as alternative encapsulation materials.